Monochorionic triamniotic triplets following conventional in vitro fertilization and blastocyst transfer - Sumana Gurunath; Adinarayana Makam; Sriprada Vinekar; Reeta H Biliangady (Wolters Kluwer Medknow Publications, 2015)
Multiple pregnancy in in vitro fertilization (IVF) is on the decline with a reduction in number of embryos transferred. But the risk of monozygotic splitting persists. The risk of monozygotic twinning in women undergoing IVF is reported to be twice that of natural conception, and monochorionic triplets are even rarer at 100 times more than natural conception. We report a case of monochorionic triamniotic (MCTA) triplets following conventional IVF and blastocyst transfer without zona manipulation. This report highlights the possibility of zygotic splitting in IVF in young couples with no family history, in centers with good experience with blastocyst transfer. MCTA triplets carry a high risk of perinatal mortality and morbidity and need multidisciplinary care. Prevention and prediction of zygotic splitting ought to be realized with better reporting and identification of possible risk factors.